2015
DOI: 10.1038/srep17574
|View full text |Cite
|
Sign up to set email alerts
|

Structural Insight into the interaction of Flavonoids with Human Telomeric Sequence

Abstract: Flavonoids are a group of naturally available compounds that are an attractive source for drug discovery. Their potential to act as anti-tumourigenic and anti-proliferative agents has been reported previously but is not yet fully understood. Targeting human telomeric G-quadruplex DNA could be one of the mechanisms by which these flavonoids exert anticancer activity. We have performed detailed biophysical studies for the interaction of four representative flavonoids, Luteolin, Quercetin, Rutin and Genistein, wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
35
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(39 citation statements)
references
References 51 publications
3
35
0
1
Order By: Relevance
“…Therefore, the overall stabilization in T m was of 3 °C upon quercetin binding, although further systematic studies are required. These results are consistent with our CD results which state the binding of antiparallel G4 with quercetin and previously published reports [60][61][62][63][64].…”
Section: Thermodynamic Analysis Of the Human Telomeric And Bcl2 G-quasupporting
confidence: 94%
“…Therefore, the overall stabilization in T m was of 3 °C upon quercetin binding, although further systematic studies are required. These results are consistent with our CD results which state the binding of antiparallel G4 with quercetin and previously published reports [60][61][62][63][64].…”
Section: Thermodynamic Analysis Of the Human Telomeric And Bcl2 G-quasupporting
confidence: 94%
“…Moreover in last few years various ligands with synthetic and natural origin have been reported that binds to various human G-quadruplex DNA like telomeric DNA15, promoter region of c-myc DNA16. One of such naturally available small molecule is Piperine.…”
mentioning
confidence: 99%
“…O seu potencial para atuar como agentes anti-tumorigênicos e anti-proliferativos tem sido relatado, além de ter propriedades antiviral, antifúngica, antibacteriana, vasodilatador, anticancerígeno e anti-isquêmico (32)(33)(34).…”
Section: Resultsunclassified